Advantage of wavelet technique to highlight the observed geomagnetic perturbations linked to the Chilean tsunami (2010). Issue 4 (2nd April 2014) - Klausner, V.; Mendes, Odim; Domingues, Margarete O.; Papa, Andres R. R.; Tyler, Robert H.; Frick, Peter; Kherani, Esfhan A.
<x xml:space="preserve">Abstract</x> The vertical component (Z) of the geomagnetic field observed by ground‐based observatories of the International Real‐Time Magnetic Observatory Network has been used to analyze the induced magnetic fields produced by the movement of a tsunami, electrically conducting sea water through the geomagnetic field. We focus on the survey of minutely sampled geomagnetic variations induced by the tsunami of 27 February 2010 at Easter Island (IPM) and Papeete (PPT) observatories. In order to detect the tsunami disturbances in the geomagnetic data, we used wavelet techniques. We have observed an 85% correlation between the Z component variation and the tide gauge measurements in period range of 10 to 30 min which may be due to two physical mechanisms: gravity waves and the electric currents in the sea. As an auxiliary tool to verify the disturbed magnetic fields, we used the maximum variance analysis (MVA). At PPT, the analyses show local magnetic variations associated with the tsunami arriving in advance of sea surface fluctuations by about 2 h. The first interpretation of the results suggests that wavelet techniques and MVA can be effectively used to characterize the tsunami contributions to the geomagnetic field and further used to calibrate tsunami models and implemented to real‐time analysis for forecast tsunami scenarios.